STRATEGI TRADING MATA UANG ASING (VALUTA ASING / FOREIGN EXCHANGE) - Anthon Mesakh; Ricky Ekaputra Foeh; Struce Andriyani (Universitas Nusa Cendana, 2017)
Regardless of the risks, Forex business is a profitable business instrument. Foreign currency exchange is a tradetransaction of a country currency against other currencies (currency pair) that involves major financial marketsin the world for 24 hours, so it is possible to taking profits within 24 hours. George Soros said that Forex is thegreatest money-producing machine in the world and nothing else. Each trader is required to have the foreigncurrency trading strategy to avoid the losses. In this study, researchers tried to compare between the strategies byobserving three most often strategies used by Forex traders namely ; the Martingale Trading Strategy, By NewsTrading Strategy and Pending Order Trading Strategy. The population in this research are the infinite numberof Forex traders, but its nature is homogeneous. The sampling techniques used in this research is